THE INFLUENCE OF SOCIALIZATION AND PROFESSIONALISM ON CUSTOMER DECISIONS TO USE HAJJ SAVINGS AT BANK SUMSEL BABEL SHARIA SUB-BRANCH UIN RADEN FATAH PALEMBANG - Juniawati, Mutmainah; Rahmah, Inge (Cattleya Darmaya Fortuna, 2024)
As public awareness of these goods and services has increased, Islamic banks should have the ability to provide them. Socialization activities have the potential to increase public knowledge, improving public perception of Islamic banking. The perspective of employee professionalism is very important for the selection of Hajj savings products for the community. This study involved 97 customers of Bank Sumsel Babel Syariah Capem UIN Raden Fatah Palembang. The purpose of this study was to determine how professionalism and socialization affect customers' decisions to use Hajj savings. Validity, reliability, classical assumptions, and multiple linear regression analysis and hypotheses were tested on the initial questionnaire data. The result is that socialization and professionalism have a positive impact on consumer decisions. Keywords: Customer Decision, Professionalism and Socialization